History of Masha’ir (‘Arafah, Muzdalifah and Mina) - Omer, Spahic (Dar al-Wahi Publication, 2023)
This book discusses the case of ‘Arafah, Muzdalifah and Mina - which are collectively called in Arabic al-masha’ir al-muqaddasah, or just masha’ir – during the course of some crucial periods of Muslim history. The al-masha’ir al-muqaddasah expression signifies the sacred geographical locations in the vicinity of the holy city of Makkah where a number of essential Hajj or pilgrimage rites are carried out. The discussion entails the three holy sites as geographical realities, religious concepts and symbols, and as the loci of a number of Hajj ceremonies. The key information needed for the first half of the book (Chapters One and Two) is obtained from the major works of the early Islamic geography, history and travel literature, wherein the holy city of Makkah and its pilgrimage rites have not always been the solitary point of interest. The second half of the book (Chapters Three and Four) focuses on what could be called the specialised pilgrimage literature, which in the end assumed a conspicuous transnational and multilingual character and was continuously enriched both by Muslims and non-Muslims. The main objective of the book is to demonstrate how, historically, the configurations and functions of the masha’ir – as part of a bigger Hajj pilgrimage picture – was responding to, and was coping with, the religious and other socio-political developments not only in Makkah and the Hijaz region, but also in the rest of the Muslim world. The book likewise pertains to some milestones of the civilizational evolution trajectory of Muslims, unfolding as much in the consciousness realm as in the vicissitudes of the real life. The book has four chapters. The first chapter is titled “The masha’ir in the classical Islamic sources: the role of al-Azraqi’s ‘Akhbar Makkah’ (Reports about Makkah).” The chapter analyses the role of al-Azraqi and his book “Akhbar Makkah” in safeguarding the recorded history and development of the masha’ir. The importance of al-Azraqi and his magnum opus lies in the fact that the study of the masha’ir thus became more comprehensive and more systematic, almost scientific. The book marked a turning point in the growth of the holy cities literature. The second chapter is titled “The masha’ir in the accounts of the early Muslim travellers and explorers.” The chapter discusses the Hajj events and the conditions of the masha’ir as found in the narratives of the early Muslim travellers-cum-explorers. Four celebrated personalities from the classical period are featured: al-Maqdisi or al-Muqaddasi, Naser Khosraw, Ibn Jubayr and Ibn Battuta. The chapter highlights how the masha’ir started to capture the exploratory thoughts and to command the literary attention of people. This was following the emergence of the science of Islamic geography, accompanied by the commencement of the rise of a literature on the Hajj pilgrimage in particular and on the holy cities of Makkah and Madinah in general. The third chapter is titled “The masha’ir through the eyes of two non-Muslim Western explorers: Ali Bey el Abbassi and J.L. Burckhardt.” This chapter deals with the state of the masha’ir as perceived through the eyes of two non-Muslim Western travellers and explorers: Ali Bey el Abbassi and J.L. Burckhardt. The two men have been selected because their accounts are most comprehensive, most accurate, and most unprejudiced as compared to their peers, and because their visits coincided with two perhaps most dramatic periods in the history of the Hijaz. As regards Ali Bey el Abbassi, he secretly performed the Hajj in 1807, which happened to be in the aftermath of the first Wahhabi conquest of the cities of Makkah and Madinah. On the other hand, Burckhardt performed his Hajj in 1814, which was about two years following the Ottoman recapture of Makkah from the Wahhabis. At the time of Burckhardt’s visit, there was a warfare still taking place in the Hijaz territories and beyond in the Arabian Peninsula between the Ottomans - led by the Ottoman governor and actual ruler of Egypt, Muhammad Ali – and the Wahhabis. The war was launched in 1811 and was completed in 1818 with the victory of the Ottomans. The fourth and final chapter is titled “The masha’ir and the onset of modernity.” The chapter discusses the theme of the relationship between the masha’ir and the inception of modern times. The chapter sheds some light on the first examples of the uncontainable advances of modernity and how they impacted the make-up and performances of the masha’ir. As a result, the milieu of the masha’ir was set never to be the same again. The scope of the chapter extends from the second half of the 19th century and the arrival of photography to the first half of the 20th century. The latter marked the rise of the Saudis led by Abdulaziz b. Al Saud as the founder of the Modern Saudi Arabia and its first king.